PENINGKATAN HASIL BELAJAR PEND AGAMA ISLAM PADA MATERI SHALAT JAMA’ DAN QASHAR MELALUI METODE DEMONSTRASI - Husniati Husniati (UNIVERSITAS SERAMBI MEKKAH, 2014)
Abstract Activity classroom action research was conducted at SMPN 11 Banda Aceh. As the subjects in the study of this class action is the student’s seventh of SMPN 11 Banda Aceh that the large number of student’s as many 27 people, including 11 males and 16 females. The source of data obtained in this study is the result of student learning, the observation by peers and documentation of as student’s grade on Febuary until April 2012. The result showed mastery learning in the first cycle as many as 10 student’s (37%). Once implemented the second cycle learning by implementing the method of demonstration, the student’s learning result increase of 21 student’s (77,8%) that mastery learning. This number clearly shows that there has been a significant increase from cycle I to cycle II. Based on the learning result of cycle I to cycle II mastery learning has been achieved as expected is the mastery of student’s learning result of 77,8%. Keywords: Learning result, PAI, Demonstration method.